Antecedents and impacts of trust in mobile transactions: a case study of Malaysian consumers / Mohamad Noorman Masrek, Nora'ayu Ahmad Uzir and Irni Eliana Khairuddin - Masrek, Mohamad Noorman; Ahmad Uzir, Nora'ayu; Khairuddin, Irni Eliana (Research Management Institute (RMI), 2013)
Just as the intensity of scientist investigating on advancing and sophisticating the mobile technologies, scholars and researchers alike have also been very active in studying the social aspect of the mobile usage. One of the most popular topics which has received much interest among IS researchers is the aspect of trust in using the mobile banking. There are two main actors in trust which are the trustor i.e. the trusting party, and the trustee which is the trusted party. In the context of mobile banking, the trustor would be the consumer of mobile banking services while the trustee would cover not only the retail banking that provides the mobile banking services but also the mobile telecommunication provider and the mobile telephone technology itself. The extant literature on the aspect of trust in mobile banking showed that most studies have been focusing on the retail banking and the mobile telecommunication provider only. The literature suggests that trust in technology is equally important in ensuring successful adoption of services rendered through the technology itself. Considering that very few studies have actually addressed the aspect of trust with all the three categories of trustee i.e. the retail banks, the mobile telecommunication provider and the mobile telephone in one single study, this study attempts to address this gap. In addition the study also seeks to investigate the impact of mobile banking utilization on satisfaction and loyalty. Adopting a survey research methodology involving 312 of mobile banking consumers in Malaysia, the findings suggest mobile banking utilization is positively correlated to satisfaction. The findings also show that mobile banking satisfaction does have bearing on loyalty. Three groups of antecedents namely the technology trust, trustworthiness and institution-based trust which are hypothesized to have significant influence on mobile banking utilization. The findings reveal that only technology trust and institution-based trust are found to have significant correlation with mobile banking utilizations. The findings of this study should be useful to both practitioners and researchers. As for the banking practitioners, the findings have empirically shown the importance of mobile banking services and its influence towards customer satisfaction. In the context of Malaysia, not all banks have implemented mobile banking. Hence this finding should alert banking practitioners that in line with the advancement of the ICT, they have no other choice but to embrace and implement mobile banking or otherwise they would risk of losing their customers. As for the researchers, besides replicating this study in countries that have implemented mobile banking, they should also consider employing a different research approach, such as qualitative approach so as to get richer and deeper understanding on the situation of mobile banking utilization among users. The framework used in the study could be used as the conceptual framework guiding such researches.